Radionuclide Small Intestine Imaging - Jiri Dolezal; Marcela Kopacova (Gastroenterology Research and Practice)
The aim of this overview article is to present the current possibilities of radionuclide scintigraphic small intestine imaging. Nuclear medicine has a few methods—scintigraphy with red blood cells labelled by means of Tc99m for detection of the source of bleeding in the small intestine, Meckel’s diverticulum scintigraphy for detection of the ectopic gastric mucosa, radionuclide somatostatin receptor imaging for carcinoid, and radionuclide inflammation imaging. Video capsule or deep enteroscopy is the method of choice for detection of most lesions in the small intestine. Small intestine scintigraphies are only a complementary imaging method and can be successful, for example, for the detection of the bleeding site in the small intestine, ectopic gastric mucosa, carcinoid and its metastasis, or inflammation. Radionuclide scintigraphic small intestine imaging is an effective imaging modality in the localisation of small intestine lesions for patients in whom other diagnostic tests have failed to locate any lesions or are not available.